Highly infectious diseases in the Mediterranean Sea area: Inventory of isolation capabilities and recommendations for appropriate isolation. (November 2018) - Fusco, F.M.; Brouqui, P.; Ippolito, G.; ,
Abstract: Epidemics such as viral haemorrhagic fevers, severe acute respiratory syndrome, Middle East respiratory syndrome coronavirus or yet unknown ones have few chances of disappearing. Globalization, worldwide travel, climate change, social conflicts and wars, among others, are likely to favor the emergence of epidemics. Preparedness of hospitals to prevent the spread of these outbreaks is among the prioritized political programmes of many countries. The EuroNHID network has in the past drawn a map of features and equipment of hospitals across Europe to take care of highly contagious patients. We update the data regarding isolation capabilities and recommendations, with an emphasis on Mediterranean countries.